PENGGUNAAN MEDIA PEMBELAJARAAN UNTUK MENINGKATKAN KEAKTIFAN SISWA KELAS III SDN ADIARSA BARAT IV PADA MATERI DAKWAN NABI MUHAMMAD SAW - Fanani, Dzulkifli Fahrul; Rahman, Rifqi Aulia; Amalia, Rosa; Puspitasari, Shela; ‘Atika, Risya; Khulasoh, Siti (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This study aims to develop a valid and practical mobile-based interactive learning media. The research method used is Research and Development (RD) by implementing the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The problem found in Informatics subject for class X TKJ at SMK Negeri 5 Padang indicates that practice-based learning has not been optimal, resulting in low student comprehension. Additionally, the use of information and communication technology in the learning process remains limited, and smartphones have not been fully utilized for learning purposes. The research results show that the validity level of the learning media assessed by media experts reached 91.05% with the category "Highly Valid" and is deemed feasible for use. Validation by subject matter experts obtained an average score of 89.44% with the "Highly Valid" category. Meanwhile, the practicality test by subject teachers obtained a percentage of 91.11% in the "Highly Practical" category. The practicality test by students resulted in a percentage of 86.99% in the "Highly Practical" category. Thus, this mobile-based interactive learning media can be used as an effective tool to enhance students' understanding in Informatics subjects.